The Economic Importance of Adolescent Financial Management: Self Control As An Intervention - Suryani, Devi; Apriliyana, Lisa; Mardiyani, Mardiyani (Dinasti Publisher, 2025)
This study analyzes the effect of digital payment adoption, financial literacy, and shopping behavior on adolescent financial management with self-control as an intervening variable. The research was conducted on teenagers aged 15-24 in Cirebon Regency using a quantitative questionnaire survey method. Data were analyzed using PLS-SEM. The results showed that financial literacy and shopping behavior significantly influence adolescent financial management. Good financial literacy improves adolescents' ability to budget and manage spending wisely, while controlled shopping behavior supports more effective allocation of funds. In contrast, digital payment adoption does not significantly influence financial management or self-control. Moreover, self-control acts as a mediating variable that reinforces the impact of financial literacy and shopping behavior on financial management. This research highlights the significance of financial literacy and self-control as fundamental foundations for developing healthy and sustainable financial habits among adolescent.